Simple-Structured OLEDs Incorporating Undoped Phosphorescent Emitters Within Non-Exciplex Forming Interfaces: Towards Ultraslow Efficiency Roll-Off and Low Driving Voltage for Indoor R/G/B Illumination - Xu, Ting; Yi, Ruichen; Zhu, Chunqin; Lin, Mingquan (Frontiers in Chemistry, 2021)
To meet the requirement of indoor R/G/B monochrome illumination by simplified OLEDs structure and fabricate process, herein, a design philosophy of low efficiency roll-off and simple-structure OLEDs incorporating R/G/B phosphorescent ultrathin non-doped emissive layers (EMLs) within non-exciplex forming interfaces luminescent system by direct charge trapping mechanism has been reported, which is applied bis(2-methyldibenzo[f,h]-quinoxaline)(acetylacetonate)iridium(III) (MDQ)2Ir(acac), bis(3-phenylpyridin-e)iridium(III) (Ir(ppy)3), bis(3,5-difluoro-2 -(2-pyridyl)phenyl-(2-carboxypyridyl) iridiumII) (Firpic) as R/G/B luminescent dyes, respectively. Although the recombination zone is narrow in the designed OLEDs, the efficiency roll-off of designed OLEDs are unexpectedly generally slow, which contributes to stable charge trapping to emitters and avoided concentration quenching in relatively low current density, but the luminance meets the requirement of indoor lighting. With a low threshold voltage of 2.9/2.9/3.5 V, the designed R/G/B phosphorescent OLEDs show the efficiency roll-off as low as 7.6/3.2/4.3 % at the indoor luminance from 10 cd/m2 to 1000 cd/m2, respectively. The perspective of R/G/B luminescent dyes on luminous efficiency, chromaticity coordinate drifts, efficiency roll-off and direct charge trapping is thoroughly studied. Therefore, our work may shed light on further development of ideal indoor lighting by simplified undoped R/G/B OLEDs structure with ultraslow efficiency roll-off, low threshold voltage, simplified fabrication process, low reagent consumption and cost, simultaneously.